IFN-γ and IL-10: seric and placental profile during pig gestation Seric and placental cytokines in pig gestation - Velez, Carolina (2023)
Concentration of interferon-gamma and interleukin-10 in maternal serum and in maternal and fetal porcine placental extracts from different gestation periods was determined. Crossbred pigs’ placental samples of 17, 30, 60, 70, and 114 days gestation and non-pregnant uteri were used. Interferon-gamma concentration was increased at the placental interface at 17 days, in maternal and fetal placenta, and decreased significantly in the remaining gestation periods. Interferon-gamma showed a peak in serum at 60 days. Regarding interleukin-10, placental tissue concentrations were unaltered, there were no significant differences with non-gestating uteri samples. In serum interleukin-10 increased at 17, 60, and 114 days gestation. At 17 days there are uterus structural and molecular changes that allow the embryos implantation and placenta development. The presence of interferon-gamma found at this moment in the interface would favor that placental growth. Moreover, its significant increase in serum at 60 days, would generate a proinflammatory cytokine pattern that facility the placental remodeling characteristic of this moment of porcine gestation. On the other hand, a significant interleukin-10 increase in serum at 17, 60 and 114 days could indicate its immunoregulatory role at a systemic level during pig gestation.